2015
DOI: 10.1007/s00792-015-0740-7
|View full text |Cite
|
Sign up to set email alerts
|

Unexplored Brazilian oceanic island host high salt tolerant biosurfactant-producing bacterial strains

Abstract: We aimed to isolate biosurfactant-producing bacteria in high salt conditions from uncontaminated soils on the Brazilian oceanic island, Trindade. Blood agar medium was used for the isolation of presumptive biosurfactant-producing bacteria. Confirmation and measurements of biosurfactant production were made using an oil-spreading method. The isolates were identified by fatty acid profiles and partial 16S rRNA gene sequence analysis. A total of 14 isolates obtained from the 12 soil samples were found to produce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Most of these isolates have been previously reported in marine or oceanic environments and other highly saline environments (Claverías et al 2015 ; da Silva et al 2015 ). Based on the conditions used for recovering these microorganisms, the majority of our isolates are heterotrophic, mesophilic, aerobic or facultative aerobes that are halophilic or halotolerant organisms that can cope with salt concentrations ranging from 0 to 8% NaCl (w/v).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Most of these isolates have been previously reported in marine or oceanic environments and other highly saline environments (Claverías et al 2015 ; da Silva et al 2015 ). Based on the conditions used for recovering these microorganisms, the majority of our isolates are heterotrophic, mesophilic, aerobic or facultative aerobes that are halophilic or halotolerant organisms that can cope with salt concentrations ranging from 0 to 8% NaCl (w/v).…”
Section: Discussionmentioning
confidence: 94%
“…Halophiles have attracted the interests of researchers because of their adaptability to a wide range of salinities as well as their potentially promising applications. They are sources of compatible solutes, stable enzymes (DNAses, lipases, amylases and proteases), bacteriorhodopsin, polymers, β-carotene and other organic substances of interest (Chen et al 2010 ; Oren 2010 ; Braña et al 2015 ; da Silva et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported Actinobacteria as a good option for removing recalcitrant hydrocarbon, since they are known for the production of extracellular enzymes that degrade a wide range of complex hydrocarbons. Also, many species of Actinobacteria are able to produce biosurfactants that enhance hydrocarbons solubility and bioavailability ( Pizzul, Del Pilar Castillo & Stenström, 2007 ; Kim & Crowley, 2007 ; Balachandran et al, 2012 ; Da Silva et al, 2015 ). The Actinobacteria phylum is recognized as the main alkane degrader in polar soils ( Aislabie, Saul & Foght, 2006 ), besides producing multiple types of antifungals, antivirals, antibiotics, immunosuppressives, anti-hypertensives and antitumorals ( Benedict, 1953 ; Ōmura et al, 2001 ; Khan et al, 2011 ; De Lima Procópio et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…As being previously observed by other authors, we could not observe a close link in these tests. For example, da Silva et al [ 34 ] isolated strains with hemolytic activity; however, only 33 % were confirmed as biosurfactant producers via the oil-spreading method.…”
Section: Discussionmentioning
confidence: 99%